Onset and severity of hearing loss due to congenital rubella infection. Issue 9 (September 1989) - Wild, N J; Sheppard, S; Smithells, R W; Holzel, H; Jones, G
Abstract : Of 111 children born in 1978-82 with congenital rubella infection, confirmed by the detection of rubella specific IgM shortly after birth, 68 were reported to be hearing impaired when notified to the National Congenital Rubella Surveillance Programme (NCRSP). The average age at which the diagnosis of hearing impairment was confirmed was 11.6 months. Recent audiograms showed a hearing loss that was usually uniform across all frequencies, equal in both ears and severe, averaging 93 dB across the range 250-4000 Hz. Despite the early diagnosis of congenital rubella and the known risk of deafness, only eight of 57 infants had been tested for auditory evoked responses in the first 6 months of life; all eight had severe hearing loss. Evidence of progressive hearing loss was found in only one of the 57 children. Definitive hearing tests (as distinct from screening tests) were frequently delayed until after the first birthday. Newborn babies identified as being at high risk of congenital deafness should have a full audiological assessment in early infancy.